2007
DOI: 10.1002/macp.200700342
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Ordering of Side‐Group Liquid Crystal Polymer and Small Molecule Liquid Crystal: Order and Phase Behavior of Nematic Polymer Solutions

Abstract: Addition of a small‐molecule liquid crystal (5CB) to a cyanobiphenyl‐based side‐group liquid crystal polymer (SGLCP) stabilizes nematic order, increasing the isotropization temperature (TNI) more than 15 °C. Despite synergistic ordering at high concentration, small amounts of polymer destabilize nematic order. Even though TNI(SGLCP) is 27 °C greater than TNI(5CB), 2H NMR shows that the order parameter of the SGLCP is less than that of 5CB at concentrations for which monodomains were accessible (≤10 wt.‐%). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Whereas, as noted above, the behaviors of amphiphilic polymers and monomers have been widely studied at LC interfaces, oligomers have not been investigated. Past studies have established, however, that the interactions of adsorbates/absorbates with nematic LCs are strongly dependent on the configurational degrees of freedom of the adsorbates/absorbates and the extent to which configurational degrees of freedom are modified by the orientationally ordered environment of the LCs. ,, For example, it is well-known that flexible polymers segregate from nematic LCs because the orientational order of the LC reduces the configurational degrees of freedom of the polymer chain (entropic penalty). , Accordingly, we hypothesized that the degree of oligomerization may impact the miscibility of amphiphiles with LCs and thus the response of LCs to exposure to oligomers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, as noted above, the behaviors of amphiphilic polymers and monomers have been widely studied at LC interfaces, oligomers have not been investigated. Past studies have established, however, that the interactions of adsorbates/absorbates with nematic LCs are strongly dependent on the configurational degrees of freedom of the adsorbates/absorbates and the extent to which configurational degrees of freedom are modified by the orientationally ordered environment of the LCs. ,, For example, it is well-known that flexible polymers segregate from nematic LCs because the orientational order of the LC reduces the configurational degrees of freedom of the polymer chain (entropic penalty). , Accordingly, we hypothesized that the degree of oligomerization may impact the miscibility of amphiphiles with LCs and thus the response of LCs to exposure to oligomers.…”
Section: Introductionmentioning
confidence: 99%
“…7,29,37−40 For example, it is well-known that flexible polymers segregate from nematic LCs because the orientational order of the LC reduces the configurational degrees of freedom of the polymer chain (entropic penalty). 41,42 Accordingly, we hypothesized that the degree of oligomerization may impact the miscibility of amphiphiles with LCs and thus the response of LCs to exposure to oligomers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…64,63 Indeed, the SCLCP was found to dissolve very well in the LMWLC, and the biphasic region in the phase diagram was observed to be very narrow. 30 We thus use A = 0 and a small negative value of B = −0.5/k B for the χ parameter to ensure the good solvent quality. Since the SCLCP backbone chain in the Scruggs−Kornfield experiment is long, we set N = 100 in our calculation.…”
Section: Resultsmentioning
confidence: 99%
“…25−27 While this approach can yield good agreement with the observed phase diagrams for some systems, 22,28,29 it does not consider the conformation of the SCLCP backbone and any effects originating from the coupling between the polymer backbone and the nematic order. 30,31 Another popular approach, proposed by Wang and Warner, 32 describes the SCLCP backbone using a worm-like chain model and the coupling between the backbone and side groups using a term of the Maier−Saupe form. However, this theory predicts first-order phase transitions between nematic phases with different chain conformations, but such abrupt transitions have not been observed experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Finkelmann et al have shown that the block copolymer segment containing the mesogenic moieties feature a selective solubility in the low molecular weight liquid crystals, whereas the isotropic block is not soluble in the LC solvent [13]. As a result, the flexible segments of an AB-diblock copolymer associate and form a micelle core that is surrounded by a corona of soluble liquid crystalline blocks [14][15][16].…”
Section: Introductionmentioning
confidence: 97%